The Influence of Learning Models Inquiry Training Regarding the Learning Outcomes of Class Ix Students at SMP Negeri 5 Sumenep - Fauzan, Ahmad; Prihandono, Trapsilo; Bektiarso, Singgih (International Journal of Education, Information Technology, and Others, 2024)
This study aims to determine the effect of the Inquiry Training learning model on the Learning Outcomes of Class IX Students of SMP Negeri 5 Sumenep. The research method used is a quasi experiment. The research design used is nonequivalent control group design. The sample in this study were students of class IX A as an experimental class totaling 31 students and class IX C as an experimental class totaling 30 students. The research instrument used was a description test question to see student learning outcomes. The results of the Independent Sample T-Test hypothesis test showed a significance value of 0.008 <0.05 which states that H0 is rejected and H1 is accepted so it can be concluded that the use of the Inquiry Training learning model has a significant effect on student learning outcomes on Electrical Circuit material